The Effect of Destination Image on Trust with Satisfaction as a Mediating Variable (a Study of the Tourist Village of Aengtongtong) - Fauziyah, Nurul Laili; AS, Fathor (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This research examines how destination image influences tourist trust, with satisfaction serving as a mediating variable in the Aengtongtong Keris Tourist Village. The study addresses inconsistencies in prior research regarding both the direct and indirect effects of destination image on trust, especially within culturally based tourist villages. The objective is to determine whether destination image affects trust directly or operates through satisfaction. Using a quantitative method and purposive sampling, data were collected from 96 respondents and analyzed using PLS-SEM. The finding revealed that destination image significantly influences satisfaction but does not directly affect trust. Satisfaction is significant and positively influences trust and acts as an effective mediator between destination image and trust. These results show that a favorable destination image must be accompanied by satisfying tourist experiences to foster trust. Theoretically, this research enriches the understanding of trust formation mechanisms in village tourism, while practically offering managers insights to enhance service quality. This study is limited to one tourist village and relies on self-reported data, suggesting opportunities for broader future research.